Conocimiento empresarial y factores que limitan el crecimiento de empresas participantes en la feria Shine - Iquitos año 2022 - Perez Arevalo, Michelle (2022)
In the world, the growth of ventures is increasingly noticeable, they help boost the economy in different countries around it, however, their prevalence in the market is minimal and worrying, so in recent years ventures have been presented that they cannot develop or fail after a time in the market, the lack of human capital, the lack of cultural identity, and the lack of knowledge about business regulations, the study raised as a general objective in the identification of business knowledge of the fair Shine and the factors that intervene for its growth of its own business, the type of study design is non-experimental of a descriptive type; the study population is made up of 20 participants of the fair, the technique used was the survey and the study instrument was the questionnaire with a reliability of 0.876 in the cronbach alpha with 32 elements, qualifying as very good, it was identified that 67 % of entrepreneurs on average present an acceptable level of knowledge in relation to planning, organization, financial tools, management and business regulations, in addition we identified four internal and external factors that have a high degree of importance in the study, it is relevant to indicate that the internal factor of human capital and suppliers present the greatest and least relevance and in the case of external factors are the economic and political factors.